Financing of fossil fuel companies by Polish banks - Korzeb, Zbigniew; Niedziółka, Paweł (Finansowanie przedsiębiorstw sektora paliw kopalnych przez banki w Polsce, 2022)
The aim of this paper was to verify the hypothesis regarding the positive impact of the changes in credit policies declared by banks in Poland on energy transition by limiting in an absolute sense the exposures to coal-based energy companies. The paper uses a simulation method for the payback period of debt financing, enhanced by scenario analysis. The analysis of the payback period of the interest-bearing liabilities indicates a horizon that will not exceed seven years from the end of 2020. This is consistent with the banks’ declarations as to when they will stop financing coal-fired power generation, but this will happen on condition that the energy companies significantly reduce their capital expenditure (actually to the level of replacement expenditure). This scenario, however, rules out a transformation of these concerns to become producers of energy from a broad spectrum of sources, and a systematic increase in the share of renewable energy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 59-73
Keywords: bank; fossil fuel sector; climate change; sustainable development; sektor paliw kopalnych; zmiana klimatu; rozwój zrównoważony